The Legal Nature of Public Property with Economic Use in Iraq - Trad, Khalid M. (PROSPECTIVE RESEARCHES, 2026)
Public property with economic use in Iraq retains its status as public funds even when utilized to generate financial resources, provided that such use is dedicated to serving the public interest and remains under state supervision. Economic use differs from traditional public use in that it aims to achieve additional financial benefits for the state without compromising the general purpose of the property. The administration adheres to the principles of transparency, equality, and legality when granting usufruct rights or entering into economic contracts, thereby preserving the public character of the property and protecting it from unlawful exploitation. The state bears direct responsibility for managing these properties and ensuring their economic use in a manner that balances the enhancement of financial resources with the protection of the public interest, while respecting public rights and complying with applicable legal rules.